Development of a plant-based meat product supplemented with red amaranth antioxidants for the elderly - Pornhathai Putthawan,; Surachai Chaiso, (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study was aimed at developing a protein-rich food formulation for the elderly using ingredients derived from soybean, sacha inchi, wheat flour, quinoa, and perilla seed. First, the protein content of all ingredients was analyzed. The results showed that the highest protein level (48.54%) was seen in sacha inchi. Then, sensory test by elderly adults was evaluated. The formulation which had the highest sensory acceptance comprised 33% soybean, 40% sacha inchi, 20% wheat flour, 5% quinoa, and 2% perilla seed. The effect of stabilizers (xanthan gum and sodium alginate) at levels of 0.1 and 0.2%, respectively, was studied. It was found that 0.1% sodium alginate produced the highest sensory score. Measurements of the texture and water absorption of the formulation showed that the values for hardness, cohesiveness, springiness, adhesiveness, chewiness and gumminess were 1003, 0.25, 0.45, 0.17, 110, and 222, respectively, while water absorption was 51.10%. An aqueous extract of Amaranthus dubius was subjected to analysis of levels of polyphenols and anthocyanins, as well as antioxidant capacity and cytotoxicity. The aqueous extract had polyphenol, anthocyanin, DPPH radical-scavenging and FRAP levels of 41.13 μg GAE/mL, 458 mg/L, 62.7%, and 14.8 μg Trolox/mL, respectively. At a concentration of 2000 μg/ mL, the crude extract exerted 22% average anti-proliferative effect on P388, KB, Hela and HepG2 cells. Different extract levels were added to the product, and the acceptability of the concentrated extract was re-evaluated. The results showed that the concentrated extract at 0.5% level of incorporation had the highest acceptance rating as a meat analogue. The energy per 100 g of the plant meat sample was 247.95 kcal, while its contents of protein, fat, carbohydrate, ash, and dietary fibre were 24.71, 6.27, 23.17, 2.52 and 6.76%, respectively. Thus, the plant meat product supplemented with A. dubius extract could be an alternative and safe diet for the elderly.